2019
DOI: 10.5455/javar.2019.f375
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morpho-histological analysis on the vomeronasal organ and the accessory olfactory bulb in Balady dogs (Canis familiaris) and New Zealand rabbits (Oryctolagus cuniculus)

Abstract: Objective:This study investigated the comparative morphological analysis of the vomeronasal organ and the accessory olfactory bulb in dogs and rabbits.Materials and Methods:A total of 15 heads obtained from each adult healthy Balady dog (Canis familiaris) and New Zealand rabbit (Oryctolagus cuniculus) of both sexes. The animals were sedated and anesthetized. Then, the heads were removed for computing topography, gross, and cross-sectional anatomy and histological techniques.Results:The vomeronasal organ was bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
(53 reference statements)
3
7
1
Order By: Relevance
“…A small median diamond‐shape prominence, the incisive papilla, was located just caudal to the secondary incisors. In accordance with that of Mahdy, El behery, and Mohamed (2019), who reported that the incisive papilla is flanked on both side by a groove on which the oral orifices of the nasopalatine ducts were opened. The nasopalatine ducts pass dorsocaudally through the palatine fissure to open into the floor of the nasal cavity providing a connection between the oral cavity and the nasal cavity (Mahdy et al, 2019; Villamayor, Cifuentes, Fdz.‐de‐Troconiz, & Sanchez‐Quinteiro, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A small median diamond‐shape prominence, the incisive papilla, was located just caudal to the secondary incisors. In accordance with that of Mahdy, El behery, and Mohamed (2019), who reported that the incisive papilla is flanked on both side by a groove on which the oral orifices of the nasopalatine ducts were opened. The nasopalatine ducts pass dorsocaudally through the palatine fissure to open into the floor of the nasal cavity providing a connection between the oral cavity and the nasal cavity (Mahdy et al, 2019; Villamayor, Cifuentes, Fdz.‐de‐Troconiz, & Sanchez‐Quinteiro, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with that of Mahdy, El behery, and Mohamed (2019), who reported that the incisive papilla is flanked on both side by a groove on which the oral orifices of the nasopalatine ducts were opened. The nasopalatine ducts pass dorsocaudally through the palatine fissure to open into the floor of the nasal cavity providing a connection between the oral cavity and the nasal cavity (Mahdy et al, 2019; Villamayor, Cifuentes, Fdz.‐de‐Troconiz, & Sanchez‐Quinteiro, 2018). The duct allows the passage of chemosignal form of pheromones together with aspirated air from the rabbit mouth into the nose through the vomeronasal organ (Villamayor et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The heights of the respiratory epithelia were 31.15±0.71 µm in male and 29.75±0.79 µm in female at the rostral portion, meanwhile those in middle portion were 31.09±0.86 µm in male and 31.09±0.80 µm in female. This result dissimilar to results of adult mammals recorded by (5) , (6) , (17) , (20) , (21) , (22) (23) , (25) , (29) and (30) . The current results suggested that the respiratory epithelium has displayed few population of goblet cells, this feature revealed that the function of new born lamb vomernasal organ could be limited because that the mucous secretion of the goblet cells is so important as a part of mechanical apparatus of pumping system, this observation is supported (10) and (26) .…”
Section: Resultscontrasting
confidence: 99%
“…The epithelia were similar those in adult mammals which mentioned by all authors with exception in newly born lamb the epithelia were revealing still differentiation (Late morphogenesis, transformation and growth). This result has recorded by (13) in Gazelle, (6) in Ox, (17) in buffalo, (18) , (19) in camel, (5), (9) in sheep, (20) , (21) in canine, (12) in equine, (22) in male red fox, (23) in Adult Guinea pig, (24) in giraffe, (25) in bear. On other hand this result disagrees with (26) in goat, (12) in horse who mentioned that the respiratory epithelium is only type in rostral portion of organ.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation